Band Gap Tuning in Composites of Polypyrrole Derivatives and C60Pd3 Polymer as Models for p–n Junction: A First Principle Computational Study. Issue 2 (9th January 2018) - Goclon, Jakub; Winkler, Krzysztof
Abstract: In this work, the electronic properties of a substituted polypyrrole (PPy−R) deposited on a palladium–fullerene polymer (C60 Pd2 (‐2Pd)) were obtained by first principles DFT+vdW calculations. By introducing both electron‐withdrawing (COOH) and electron‐donating (NH2 ) substituents into the polypyrrole chain, we modulated the HOMO and LUMO levels of PPy−R/C60 Pd2 (‐2Pd). Furthermore, we also determined the influence of the second COOH group in each pyrrole ring and the CH3 group linked to the nitrogen atom on the electronic properties. The calculated data show that the type of substituent, as well as the termination of the palladium–fullerene polymer, strongly influences the band gap. The general picture of the mixed systems reveals that the HOMO corresponds to that of PPy/PPy−R and the LUMO corresponds to that of C60 Pd2 (‐2Pd). For isolated PPy−R, the substituent strongly influences the relative position of the HOMO and LUMO levels toward the vacuum level, and, based on this fact, we can easily tune the band gap of the mixed systems. For the sake of completeness, all configurations, as well as the corresponding total binding energies, were carefully analysed and compared. The adsorption of PPy(‐R) on the Pd‐terminated C60 Pd2 led to the formation of surface Py⋅⋅⋅Pd complexes that have higher binding energies than in the case of the C60 ‐terminated polymer. Furthermore, composites with two PPy chains on C60 Pd2 (‐2Pd) were also studied. Abstract : The electronic properties of a substituted polypyrrole deposited on a palladium‐fullerene polymer were studied by first principles DFT+vdW calculations. The charge distribution at the interface between p‐ and n‐type materials and the electronic structure are a major factor determining practical applications of p‐n junction in number of technological fields. The calculated data show that the type of substituent, as well as the termination of the palladium‐fullerene polymer strongly influences the band gap.